Antiretroviral concentrations in the presence and absence of valproic acid. (25th March 2020) - Calcagno, A; Cusato, J; Ferrara, M; De Nicolò, A; Lazzaro, A; Manca, A; D'Avolio, A; Di Perri, G; Bonora, S
Abstract: Objectives: An unexpected drug–drug interaction has been recently reported between dolutegravir, an HIV integrase inhibitor, and valproic acid. Despite there being several potential underlying mechanisms, plasma protein displacement has been suggested. The aim of this study was to assess plasma concentrations of several antiretrovirals when administered with or without valproic acid. Methods: We performed a therapeutic drug monitoring registry analysis and identified patients concomitantly taking antiretrovirals and valproic acid and without clinical affecting conditions or interacting drugs. Results: One hundred and thirty-four patients were identified. Median (IQR) age and BMI were 49.7 years (45–56) and 23.4 kg/m 2 (20.8–26.3) and 78 were male (58.2%). Despite small groups, we observed no major effect on antiretroviral exposure, even when considering highly protein-bound compounds (such as etravirine), with the exception of dolutegravir trough concentrations [median (IQR) = 132 ng/mL (62–227) in individuals on valproic acid versus 760 ng/mL (333–1407) in those not receiving valproic acid]. Conclusions: Valproic acid does not have a major effect on antiretrovirals other than dolutegravir. The mechanism of this unexpected drug–drug interaction may be the combination of protein displacement, reduced absorption and CYP3A4 induction.